2012
DOI: 10.1109/tpami.2011.222
|View full text |Cite
|
Sign up to set email alerts
|

BRIEF: Computing a Local Binary Descriptor Very Fast

Abstract: Binary descriptors are becoming increasingly popular as a means to compare feature points very fast and while requiring comparatively small amounts of memory. The typical approach to creating them is to first compute floating-point ones, using an algorithm such as SIFT, and then to binarize them.In this paper, we show that we can directly compute a binary descriptor we call BRIEF on the basis of simple intensity difference tests. As a result, BRIEF is very fast both to build and to match. We compare it against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
471
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 693 publications
(491 citation statements)
references
References 35 publications
3
471
0
7
Order By: Relevance
“…-We demonstrate that, despite learning a separate representation for each individual keypoint similar to [3,8,9,19], our approach does not require a brute-force search in a large descriptor set when coupled with the LSH [2] approach to compute the list of K near neighbors. -We show that our approach is relatively descriptor independent and it extends the matching range of several binary descriptors: BRIEF [5], ORB [21], BRISK [10], FREAK [1], and LATCH [11], which has recently been shown to outperform state-of-the-art binary descriptors.…”
Section: Figmentioning
confidence: 78%
See 2 more Smart Citations
“…-We demonstrate that, despite learning a separate representation for each individual keypoint similar to [3,8,9,19], our approach does not require a brute-force search in a large descriptor set when coupled with the LSH [2] approach to compute the list of K near neighbors. -We show that our approach is relatively descriptor independent and it extends the matching range of several binary descriptors: BRIEF [5], ORB [21], BRISK [10], FREAK [1], and LATCH [11], which has recently been shown to outperform state-of-the-art binary descriptors.…”
Section: Figmentioning
confidence: 78%
“…5 Recognition rate improves when we exploit the information in the first ten near neighbors as opposed to using just the nearest neighbor. Note that the improvement is most significant when the recognition rate is low (3)(4)(5)(6) and the number of matches may not be enough for correct registration of the test image. The performance improves as M is increased from 4 to 8, however increasing M beyond 10 degrades performance due to the exponentially increasing number of parameters in the probabilistic model that requires even more training data.…”
Section: Recognition Rate Over Ground Truth Correspondencesmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, Larsen et al [81] made use of multi-local N-jet descriptors that do not rely on a spatial statistics of receptive field responses as used in the SIFT and SURF descriptors or their analogues. A notable observation from experimental results is that very good performance can be obtained with coarsely quantized even binary image descriptors (Pietikäinen et al [131], Linde and Lindeberg [88], Calonder et al [26]). Moreover, Zhang et al [158] have demonstrated what can be gained in computer vision by considering biologically inspired image descriptors.…”
Section: Related Workmentioning
confidence: 99%
“…ORB [10] and BRISK [11] speed-up feature detection and description by combining modifications of the FAST corner detector [12] and binary descriptors based on BRIEF [13] with scale and rotation invariance. ORB and BRISK feature are much faster to compute than SIFT and SURF, while showing comparable performance.…”
Section: Introductionmentioning
confidence: 99%